LATGALIAN LITERATURE AND HISTORY OF LATVIAN LITERATURE – TRADITION AND PERSPECTIVES - Kušnere, Sigita (Via Latgalica, 2017)
Latgalian literature has received relatively little attention in most studies of Latvian literature, regardless of the time or the type of the studies made, be they studies of individual or collaborative nature. In the late 19th century and early 20th century, it was largely caused by prohibition of Latgalian publications printed in the Latin alphabet. In the following periods Latgalian literature was overlooked because of lack of awareness, sometimes, also by deliberate ignorance, which was dictated by the political situation. Exploration of the current situation is the goal of this study, namely, to present a summary of what has already been accomplished and to indicate the directions where new studies are urgently needed, ideally – through joint examination of Latvian and Latgalian literatures. The summary is based on the analysis of the regularities and main issues found in the works on the history of Latgalian literature. Careful analysis of the literary processes, authors and significant literary works of the late 19th and early 20th centuries, as well as their exposure in the studies of the history of Latvian literature reveals that a short insight in publishing of Latgalian books and periodicals was given, for instance, by Teodors Zeiferts in his fundamental study ‘History of Latvian Literature, Part 2 and 3’ (Latviešu rakstniecības vēsture, 1923, 1925), and Jānis Niedre in ‘Latvian Literature. Part 2’ (Latviešu literatūra, 1953); small essays were also included in the volumes of the collaborative study developed under Ludis Bērziņš’ chief editing ‘History of Latvian Literature’ (Latviešu literatūras vēsture, 1935–1937). However, Latgalian literature was hardly mentioned in the textbooks for the secondary schools (Vilis Plūdons ‘History of Latvian literature for secondary schools, Part 1 and 2’ (Latvju literatūras vēsture vidusskolām, 1927, 1928); Roberts Klaustiņš ‘History of Latvian Literature’ (Latviešu rakstniecības vēsture, 1907)). Neither was it paid any attention by Andrejs Upīts in his ‘History of Contemporary Latvian Literature’ (Latviešu jaunākās rakstniecības vēsture, 1885–1910 (1911)). This leads to a conclusion that the attitude towards the literature written in Latgalian was ambiguous in the first half of the 20th century as it was not fully incorporated in the conceptual analysis of the development processes of Latvian literature. The voluminous ‘History of Latvian Literature’ (Latviešu literatūras vēsture, Volume 1–6, 1956–1963), which was developed during the Soviet period, included depiction of several Latgalian writers: such as Andrivs Jūrdžs and Pīters Miglinīks (Volume 2, 1963); nevertheless they did not provide a sufficient overview of the singularity and development of Latgalian literature and its comparability with the history of Latvian literature. In the editions of the history of Latvian literature, which were written after regain of the national independence, Latgalian literature has not received any focused attention either by the authors of the 3-volume ‘History of Latvian Literature’ (Latviešu literatūras vēsture, 1998–2001) or by, for instance, Guntis Berelis in his monograph study ‘History of Latvian Literature, from the First Writings to 1999’. Having gained no wide coverage in the historical studies of Latvian literature, Latgalian literature has been fundamentally researched in several monographic works of Miķelis Bukšs, Francis Kemps, Janīna Kursīte, Valentīns Lukaševičs, Ilona Salceviča, Alberts Sprūdžs, Anna Stafecka, Vitolds Valeinis and other researchers at various time periods. Nonetheless, the question still stands: whether and how to compare and synchronise Latgalian literature with periodisation and trends of Latvian literature in order to include it in the comprehensive overview of the literature history.